Implementation of a parent training intervention (SPARCK) to prevent childhood mental health problems: study protocol for a pragmatic implementation trial in Norwegian municipalities - Anette Arnesen Grønlie; Agathe Backer-Grøndahl; Ragnhild Bang Nes; Maria Begoña Gomez; Truls Tømmerås (Trials)
Abstract Background Effective evidence-based interventions (EBI) are necessary to prevent and avoid negative life trajectories for children with mental health problems. Even though many EBIs prove effective when tested, few are successfully implemented and used in real-world clinical practice. As a result, many children and families do not receive the best care in due time or at all. To reduce this research-practice gap, a combined RCT and implementation study of Supportive Parents—Coping Kids (SPARCK), a parent training intervention to prevent childhood mental health problems, will be performed. This study protocol concerns the implementation part of the larger effectiveness-implementation project. Methods The study is a correlational multi-site implementation study of SPARCK performed alongside a two-armed RCT, in 24 Norwegian municipalities. A quantitative three-wave longitudinal web-based data collection will be conducted among SPARCK practitioners and leaders in relevant services. We will investigate the relations between theory-driven and empirical implementation determinants and implementation outcomes, measured by fidelity, acceptability, appropriateness, and feasibility. In addition, we will examine how these implementation determinants and outcomes are associated with the clinical outcomes of SPARCK. Discussion The current study will investigate implementation determinants and their relation to indicators of implementation success, while simultaneously investigating effectiveness of an intervention optimized to the needs of both the target group and relevant stakeholders. Together, this may improve clinical effect, contextual fit, implementation success, and reduce the time lag between research findings and application in real-world settings. Trial registration ClinicalTrials.gov NCT05800522. Registered on 2023.03.23.